Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Konsumen Di Seblak Pasta Taman Siswa - Retno Septiana; Bangun Putra Prasetya (Manajemen Kreatif Jurnal, 2024)
This research aims to analyze the influence of service quality and product quality on consumer satisfaction at Seblak Pasta Taman Siswa. Service quality includes various aspects of interaction and service provided by staff to customers, while product quality is related to the taste, appearance and consistency of the seblak pasta served. The research method used was a survey with a questionnaire distributed to 120 respondents who were customers of Seblak Pasta Taman Siswa. The collected data was analyzed using multiple linear regression to determine the influence of the variables studied on consumer satisfaction. The research results show that both service quality and product quality significantly influence consumer satisfaction, with product quality having a stronger influence. These findings provide practical implications for the management of Seblak Pasta Taman Siswa to continue to improve service standards and product quality in order to increase customer satisfaction and maintain consumer loyalty.